Analysis of trabecular bone microstructure in osteoporotic femoral heads in human patients: in vivo study using multidetector row computed tomography. Issue 1 (December 2016) - Munemoto, Mitsuru; Kido, Akira; Sakamoto, Yoshihiro; Inoue, Kazuya; Yokoi, Kazuyuki; Shinohara, Yasushi; Tanaka, Yasuhito
Abstract Background Lag screw position is very important in the treatment of intertrochanteric femoral fracture to prevent complications such as screw cut-out. Current studies recommend central or inferior placement of the lag screw on the anteroposterior radiograph, and central placement on the lateral radiographs. These reports are based on radiographic evaluation, but few studies have investigated the importance of bone quality at the site of lag screw placement. In this study, we used multidetector row computed tomography (MDCT) to perform in vivo evaluation of the bone microstructure of the femoral head in patients with intertrochanteric femoral fractures. Methods This study was approved by the Ethics Committee of Okanami General Hospital. MDCT images were obtained in our hospital from ten patients who had sustained intertrochanteric femoral fracture. Patients who needed computed tomography to confirm fracture morphology were included. We defined six areas as regions of interest (ROI): ROI 1–3 were defined as the femoral head apex area, and ROI 4–6 were defined as the femoral neck area. Trabecular microstructure parameters, including mean bone volume to total volume (BV/TV), trabecular thickness (Tb.Th), trabecular separation (Tb.Sp), and structure model index (SMI), were evaluated with bone analysis software (TRI/3D-BON). Statistical analyses were performed using EZR software; each parameter among the ROIs was statistically evaluated by analysis of variance (ANOVA) and Tukey's test. Statistical significance was established atp  < 0.05. Results In the apical area, all parameters indicated that ROI 1 (superior) had the highest bone quality and ROI 2 (central) was higher in bone quality than ROI 3 (inferior). In the femoral neck, all parameters indicated that bone quality was significantly greater in ROI 6 (inferior) than ROI 5 (central). Discussion and Conclusions We could evaluate bone quality with clinical MDCT in vivo. Bone quality in the central area of the femoral head apical was greater than in the inferior area, and bone quality in the inferior area of the femoral neck was greater than in the central area. Recognizing which area of femoral head has greater bone quality may lead to a better clinical result in treating intertrochanteric femoral fracture.